Plasma antibody profiles as diagnostic biomarkers for tuberculosis - Khan, Imran H; Ravindran, Resmi; Krishnan, Viswanathan V; Awan, Irum Nawaz; Rizvi, Syed Kumail; Saqib, Muhammad Arif; Shahzad, Mirza Imran; Tahseen, Sabira; Ireton, Greg; Goulding, Celia W; Felgner, Phil; DeRiemer, Kathy; et al. (Clinical and vaccine immunology, 2011)
Two billion people are infected with Mycobacterium tuberculosis, the etiological agent of tuberculosis (TB), worldwide. Ten million to 20 million of the infected individuals develop disease per year. TB is a treatable disease, provided that it is diagnosed in a timely manner. The current TB diagnostic methods are subjective, inefficient, or not cost-effective. Antibody-based blood tests can be used efficiently and cost-effectively for TB diagnosis. A major challenge is that different TB patients generate antibodies against different antigens. Therefore, a multiplex immunoassay approach is needed. We have developed a multiplex panel of 28 M. tuberculosis antigen-coated microbeads. Plasma samples were obtained from over 300 pulmonary TB patients and healthy controls in a country where TB is endemic, Pakistan. Multiplex data were analyzed using computational tools by multivariate statistics, classification algorithms, and cluster analysis. The results of antibody profile-based detection, using 16 selected antigens, closely correlated with those of the sputum-based diagnostic methods (smear microscopy and culture) practiced in countries where TB is endemic. Multiplex microbead immunoassay had a sensitivity and specificity of approximately 90% and 80%, respectively. These antibody profiles could potentially be useful for the diagnosis of nonpulmonary TB, which accounts for approximately 20% of cases of disease. Since an automated, high-throughput version of this multiplex microbead immunoassay could analyze thousands of samples per day, it may be useful for the diagnosis of TB in millions of patients worldwide.